A research on technical analysis - Lai, Jiawen (2012)
Investors, analysts, and speculators alike have long searched for investment strategies that will accurately predict future price trends for a secured return. This research examines the effectiveness of Technical Analysis on buy and hold strategies, with a focus on the Ichimoku Kinko Hyo and the MACD indicators due to the popularity and employability among investors. We adopt an empirical approach for our study, gathering and analysing the trends on past market data of STI and SPDR STI